2015
DOI: 10.1038/labinvest.2015.33
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of urokinase in cigarette smoke extract-induced epithelial–mesenchymal transition in human small airway epithelial cells

Abstract: Urokinase-type plasminogen activator (uPA) augments inflammation and tissue remodeling during lung injury and repair. The uPA expression in small airway epithelium of chronic obstructive pulmonary disease (COPD) increases. Epithelialmesenchymal transition (EMT) is important in the small airway fibrosis of COPD. This study shows the uPA regulation in cigarette smoke extract (CSE)-induced EMT in human small airway epithelial cell lines (HSAEpiCs). uPA is overexpressed in the small airway epithelium of COPD patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 36 publications
3
17
1
Order By: Relevance
“…In addition, in vitro and in vivo studies have shown that hypoxia-inducible factor 1-a has been implicated in cigarette smoke-mediated EMT process in both COPD and lung cancer (61). Studies by Wang and colleagues (74,88,89) observed a significant correlation between activation of uPAR signaling and airway remodeling in patients with COPD. Accordingly, cigarette smoke extract-induced activation of uPAR induced EMT through phosphatidylinositol (PI) 3-Akt-dependent inhibition of GSK-3b in vitro in airway epithelial cells from patients with COPD.…”
Section: Epithelial To Mesenchymal Transitionmentioning
confidence: 99%
“…In addition, in vitro and in vivo studies have shown that hypoxia-inducible factor 1-a has been implicated in cigarette smoke-mediated EMT process in both COPD and lung cancer (61). Studies by Wang and colleagues (74,88,89) observed a significant correlation between activation of uPAR signaling and airway remodeling in patients with COPD. Accordingly, cigarette smoke extract-induced activation of uPAR induced EMT through phosphatidylinositol (PI) 3-Akt-dependent inhibition of GSK-3b in vitro in airway epithelial cells from patients with COPD.…”
Section: Epithelial To Mesenchymal Transitionmentioning
confidence: 99%
“…Similar effects of sorafenib are observed in liver (Chen et al, ) and urothelial carcinoma in situ (Steinestel et al, ) by targeting STAT3 and urokinase plasminogen activator (uPA). Targeted silencing of uPAR (uPA receptor) using small hairpin RNA inhibited EMT in cultured human small airway epithelial cells (Wang et al, ). Camara et al .…”
Section: Emt In Chronic Lung Diseasementioning
confidence: 99%
“…Urokinase structure consists of three conserved domains: (1) a growth factor-like domain (GFD, residues 1–49), (2) a kringle domain (residues 50–131), forming modular amino-terminal fragments (ATF by which uPA binds to uPAR) linked by the “connecting peptide” (CP, residues 132–158), and (3) a serine protease domain (residues 159–411) [103, 104]. The upregulation of uPA and its activity occurs during EMT and EMT-related fibrosis; however, its role is yet not clearly understood [105, 106]. First of all, extracellularly bounded to its receptor, uPA cleaves plasminogen and releases active, multipotent serine protease plasmin that in turn, mediates ECM degradation and by proteolytic cleavage of latency-associated peptide activation of TGF- β as well as MMPs from inactive zymogens [107110].…”
Section: Urokinasementioning
confidence: 99%